(untitled) (Global Journal of Management and Business Research, 2022)
Due to the geographic location Bangladesh is remarked as one of the most vulnerable countries to climate change These disasters have impacts on to the economy the environment national development and also education institution of Bangladesh This study found that due to the disaster educational institutions come across enormous losses Climate change and disaster causes huge losses to educational materials It is also found that girl students are more likely to irregular than boys and male teachers are more likely to irregular than female teachers In most of the affected institutions the evaluation of report on the losses is not maintained in a structured way Government should broadcast more awareness program about disaster and climate change Education institutions should be given proper guide line to maintain evaluation report for long term disaster risk management